Investigation of local heat treatment strategies for a multi-range capable rivet and the influence on joint formation and load-bearing capacity - Holtkamp, Pia Katharina; Kappe, Fabian; Probst, Paula; Bobbert, Mathias; Meschut, Gerson (Proceedings of the Institution of Mechanical Engineers, Part L: Journal of Materials: Design and Applications)
To reduce CO 2 emissions, the industry, particularly in the mobility sector, focuses on lightweight vehicles with multi-material structures. As thermal joining processes are reaching their limits, mechanical techniques such as self-piercing riveting are being used. One innovative solution is the versatile self-piercing riveting process (V-SPR), which combines different material combinations with a multi-range rivet. 1 The joining process is divided into the piercing process and the forming process of the rivet head to the respective sheet thickness. The rivet shaft requires sufficient strength to punch through the punch-sided sheet, and sufficient ductility of the rivet head is required to form onto the punch-sided sheet. To achieve a combination of these requirements, local inductive heat treatment strategies are used for the rivet. To ensure reproducible rivet hardening, a specialised device has been developed for precise rivet positioning in the induction coil and the subsequent quenching process. The heat treatment differs in terms of hardening times and temperatures. In addition, the heat treatment is combined with a subsequent tempering process. The study aims to determine the resulting hardness distributions and microstructures of the rivet and to investigate the influence of different heat treatment strategies on joint formation and load-bearing capacities. The results show that a graded hardening profile has a positive effect on the spreading behaviour of the rivet foot and the forming behaviour of the rivet head. Furthermore, the load-bearing behaviour of the joints is increased.

Investigation of the impact of a rotationally superimposed punch stroke on the binding mechanisms of a clinched joint - Lüder, Stephan; Wolf, Eugen; Schmale, Hans Christian; Brosius, Alexander (MATEC Web of Conferences)
This paper examines the impact of a rotationally superimposed punch stroke on the binding mechanisms of clinched joints of aluminum sheets. As part of the development of a method for ensuring the versatility of clinching, an additional rotational movement of the punch was introduced as a control variable to influence friction in the mechanical joining process. The effect of rotational superimposition on the force-displacement curve of the clinching processes was investigated using four test variants with different kinematics. The primary objective was to evaluate the binding mechanisms that maintain the integrity of the clinched joint. To evaluate the force closure of the resulting joint, two testing methods were employed throughout the course of the research, non-destructive resistance measurement using four-wire sensing method and destructive torsion testing. A crucial factor influencing the efficacy of the process is surface cleanliness, as contaminants between joining partners can impede the effectiveness of the clinched joint. Therefore, all specimens were meticulously cleaned prior to experimentation. This method exhibits promising potential in creating clinched joints that align with the demands of flexible manufacturing environments.
Keywords: Joining; Sheet Metal; Tribology; Clinching

Is Tax Transfer Pricing Harmonization a Panacea? Real Effects of Global Tax Transparency and Standards Consistency - Diller, Markus; Lorenz, Johannes; Schneider, Georg; Sureth-Sloane, Caren (The Accounting Review)

Islam II - Paul, Jürgen; Schneider, Irene; Kokew, Stephan; Malik, Jamal; Schulze, Fritz; Günther, Sebastian; Schrode, Paula; Rebstock, Ulrich; Gharaibeh, Mohammad; Würsch, Renate; Rudolph, Ulrich; Reichmuth, Stefan; et al.

Kausalität im Längsschnitt. Funktionen und Formen von weil, denn, deshalb, deswegen, nämlich und da in der Textproduktion vom 4. bis zum 6. Schuljahr - Topalovic, Elvira; Drepper, Laura; Blachut, Alisa (Semantische Phänomene lehren und lernen. Linguistische Berichte (LB))

KI außer Kontrolle - Hälterlein, Jens (AUSDRUCK - Das IMI-Magazin)

Kinder- und Jugendtheologie und Tradition. - Reis, Oliver (Was hat das mit zu tun? Zugange zur Tradition in der islamischen Religionspädagogik)

Kinderlyrik als soziale Praxis am Beispiel von Arne Rautenbergs Lyrikbänden Mut ist was Gutes (2023) und Sekundenfrühling (2023) - Jagdschian, Larissa Carolin (Arne Rautenbergs und die (Kinder-)Lyrik der Gegenwart)

Klagende Robben. Environmental Sound Art und das Problem der Anwaltschaft - Spieker, Jonas (Non*binär! Sound und Gender im Posthumanismus)

Kollegiales Feedback in der Hochschullehre - Osthushenrich, Judith (Praxishandbuch Hochschullehre II - Bewertung, Digitalisierung und Barrierefreiheit)
Was macht gelungene Hochschullehre aus? Und an welchen Stellschrauben kann ich drehen, um die eigene Lehre zu verbessern? Das zweibändige "Praxishandbuch Hochschullehre" bietet als Standardwerk Orientierung bei didaktischen Fragen und beleuchtet aktuelle Entwicklungen des Bereichs. In Band II setzen sich die Beiträger:innen mit dem Prüfen und Bewerten von Studierenden auseinander, geben Tipps zu Feedback und Evaluation und widmen sich den Themen Digitalisierung, Nachhaltigkeit sowie Barrierefreiheit. Angereichert mit Abbildungen, Definitionen, Schlagworten, Schritt-für-Schritt-Anleitungen und einem umfangreichen Glossar lädt der anwendungsorientierte Leitfaden alle Lehrenden dazu ein, sich aktiv mit den wesentlichen Inhalten der Hochschullehre auseinanderzusetzen – unabhängig von Fachrichtung und Erfahrungsstufe. utb+: Zusätzlich zum Buch stehen zu einigen Beiträgen hilfreiche Materialien wie Verlaufsprotokolle, Vorbereitungs- und Bewertungsbögen zum Download bereit. Verfügbar in drei Ausgabearten: Print, E-Book (PDF), Web-Book (Buch als Website). Das Web-Book integriert Buchinhalte und digitale Elemente. Für Print und E-Book sind die digitalen Materialien über utb.de kostenlos abrufbar.

Kölner Vorherrschaft über Westfalen? Zu den Ambitionen der Erzbischöfe von Köln (1188–1220) - Schreckenberg, Carolin (775 – Westfalen. Das Buch. Eine Region wird gemacht)

Kommunale Wasserregime - Wasser und Macht in der europäischen Stadt 1300-1900

Komplexität beherrschen, Kreisläufe schließen: Soziotechnische Systeme für ressourceneffiziente Leichtbaustrukturen ; Das interaktive Whitepaper
Im Rahmen des BMBF-Forschungsvorhabens KORESIL wurden entlang einer beispielgebenden Prozesskette für hybride Leichtbaustrukturen notwendige Forschungs- und Entwicklungsschwerpunkte ermittelt. Insbesondere die Steigerung der Ressourceneffizienz und die Unterstützung des Menschen im Kontext zukünftiger Arbeitsumfelder standen dabei im Mittelpunkt der Arbeiten. Hierauf aufbauend konnten Handlungsempfehlungen für Wirtschaft, Wissenschaft und Politik abgeleitet werden. Das Projekt KORESIL ist eingebettet in das Projektnetzwerk des Forschungs- und Technologiezentrums für ressourceneffiziente Leichtbaustrukturen – FOREL. Dieses Zentrum wurde im Jahr 2013 als BMBF-Leuchtturmprojekt eingerichtet und ist eine offene, unabhängige Plattform zur Entwicklung von Hightech-Leichtbausystemlösungen in Multi-Material-Design für die Mobilität der Zukunft. Ziel der Plattform ist die Unterstützung von Entwicklungsprojekten, die Vernetzung der Leichtbauforschung innerhalb Deutschlands und die Zusammenführung verschiedener Förderinitiativen.

Konzept und Wirkungen eines Lehrmoduls zur demokratischen Erarbeitung von Beurteilungskriterien in bildungswissenschaftlichen Seminaren des Lehramtsstudiums - Wehde, Janis

Konzeptionierung eines digitalen Wissensmanagementsystems für die zivile Gefahrenabwehr am Beispiel der Feuerwehr - Schultz, Andreas Maximilian
Wissensmanagement ist im unternehmerischen Kontext ein etabliertes Feld der Forschung und Praxis, das auf die Verbesserung von Effizienz und Wettbewerbsfähigkeit abzielt. In den Organisationen der zivilen Gefahrenabwehr hingegen gibt es erhebliche Defizite bei der Erfassung und Weitergabe von Wissen, obwohl auch hier große Abhängigkeiten vom Erfahrungswissen bestehen. Diese Arbeit analysiert am Beispiel der Feuerwehr die Gründe für diese Diskrepanz und entwickelt ein Konzept, das das Wissensmanagement im Feuerwehrwesen nachhaltig verankern soll. Eine deutschlandweite Umfrage mit 577 Einsatzkräften ergab, dass eine digitale Verwaltungsunterstützung bereits verbreitet ist, das Wissen jedoch vornehmlich per E-Mail, Chat, mündlich oder per Aushang verteilt wird. Die Teilnehmenden wünschen sich eine Lösung für das Wissensmanagement, die im Einsatz, bei Aus- und Weiterbildung sowie der Verwaltungsarbeit unterstützt. Auf der Umfrage und einer systematischen Literaturrecherche aufbauend, wurde der Handlungsbedarf identifiziert. Darauf basieren die Ableitung der Anwendungsbereiche sowie Rahmenbedingungen, welche sich in den Anforderungen an ein Wissensmanagementsystem widerspiegeln. Das Umsetzungskonzept beschreibt die Systemarchitektur der Lösung, die auf einem open-source Wiki mit passenden Erweiterungen beruht. Zentrales Element ist die Möglichkeit zum Austausch von Wissen über Organisationsgrenzen. Abgeschlossen wird die Arbeit mit der Demonstration und Evaluation der Lösung.

Körperbilder und Social Media im Sportunterricht. Herausforderungen und Chancen für Lehrkräfte - Grimminger-Seidensticker, Elke; ComeNet 5, Autorengruppe (sportunterricht)

Körperbilder und soziale Medien im Sportunterricht. Ist ein schöner Körper ein gesunder Körper? - Grimminger-Seidensticker, Elke; Voogd, Andreas; Krückels, Manuel (sportunterricht)

Krisen historischen Lernens. Zum historischen Lernpotenzial sprachlich-interaktionaler Krisen im Geschichtsunterricht. - Pilz, Franziska (Theorie und Empirie - ein unzertrennliches Paar? Tagung der Early Career Researcher der Konferenz für Geschichtsdidaktik in der Universität Bielefeld 2023)

Künstlerische Zusammenarbeit zwischen Ehekonvention und Sublimation. Hans Werner Henzes Bühnenschaffen mit Ingeborg Bachmann, W.H. Auden und Chester Kallman - Tumat, Antje ((Wahl-)Verwandtschaften.Gemeinschaftliches kulturelles Handeln)
A preference for music theatre works is characteristic of Hans Werner Henze's oeuvre, as is his close collaboration with famous 20th-century authors, who wrote the libretti for his music theatre works. This paper explores the artistic collaborations of Hans Werner Henze and Ingeborg Bachmann on the one hand and Henze, Chester Kallman and W.H. Auden on the other in the context of their joint operatic work, surviving correspondence and poetological essays. This is set against the backdrop of how personal relationships can influence collaboration in the performing arts. In both cases, the letters and biographical writings of the aforementioned working groups, read from a gender perspective and with regard to creativity, forms of relationship and artistic collaboration, point to a tension between potential and desired personal relationships, the confrontation with marriage as a conventional social framework and artistic collaboration as a long-term connection.

Künstliche Intelligenz - Überlegungen zum Einsatz von ChatGPT im Pädagogikunterricht aus Perspektive der Medienbildung - Engemann, Mario (Zeitschrift PädagogikUNTERRICHT)

Künstliche Intelligenz und professionsbezogene Aufgaben von Lehrkräften - Herzig, Bardo (SchulVerwaltung)

Langrezension zu Matthias Bau et al (Hg.) 'Vergessene Klassiker der Sprachwissenschaft? Zur Einführung und Erinnerung` - Markewitz, Friedrich (Zeitschrift für Rezensionen zur germanistischen Sprachwissenschaft)

Lead-Free Ceramics in Prestressed Ultrasonic Transducers - Scheidemann, Claus; Bornmann, Peter; Littmann, Walter; Hemsel, Tobias (Actuators)
Today’s ultrasonic transducers find broad application in diverse technology branches and most often cannot be replaced by other actuators. They are typically based on lead-containing piezoelectric ceramics. These should be replaced for environmental and health issues by lead-free alternatives. Multiple material alternatives are already known, but there is a lack of information about their technological readiness level. To fill this gap, a small series of prestressed longitudinally vibrating transducers was set up with a standard PZT material and two lead-free variants within this study. The entire process for building the transducers is documented: characteristics of individual ring ceramics, burn-in results, and free vibration and characteristics under load are shown. The main result is that the investigated lead-free materials are ready to use within ultrasonic bolted Langevin transducers (BLTs) for medium-power applications, when the geometrical setup of the transducer is adopted. Since lead-free ceramics need higher voltages to achieve the same power level, the driving electronics or the mechanical setup must be altered specifically for each material. Lower self-heating of the lead-free materials might be attractive for heat-sensitive processes.

Lehrkräftebildung in NRW: bildungsgerecht, digital, ko-konstruktiv. Ein standortübergreifendes bildungswissenschaftliches Seminarkonzept auf der Basis eines MOOCs - Endberg, Manuela; Bellenberg, Gabriele; Schulze-Uludasdemir, Johanna; Eickelmann, Birgit (Bildungsforschung und Bildungspraxis in der Metropole Ruhr. Schule und Lehrkräftebildung gemeinsam im regionalen Kontext entwickeln)

Lehrkräftekooperation und Digitalisierung. Digital-kooperative Arbeitsbeziehungen im Schulfach Erziehungswissenschaft - Engemann, Mario
Die Herausforderungen des digitalen Transformationsprozesses tangieren das öffentliche und private Leben – davon ist selbstredend auch die Schule und der Unterricht betroffen. Zugleich gilt die Lehrkräftekooperation als eine Möglichkeit, um gesellschaftlichen Herausforderungen in Schulen begegnen zu können. Davon ausgehend untersucht Mario Engemann die digital-kooperativen Arbeitsbeziehungen von Lehrkräften – exemplarisch am gymnasialen Schulfach Erziehungswissenschaft. Unter Rückgriff auf ein Mixed-Methods-Design beantwortet er die Frage, wie sich die Lehrkräftekooperation hinsichtlich der Digitalisierung in Formen, Gestaltung und Rahmenbedingungen darstellt. Die empirische Datenbasis der Arbeit bilden ein eigens unter Berücksichtigung bestehender Items zur Lehrkräftekooperation konzipierter quantitativer Fragebogen sowie Expert*inneninterviews mit Lehrkräften.
Keywords: Bildungsforschung; Medienpädagogik; Lehrerkooperation; Digitalisierung; Schulfach Erziehungswissenschaft

Leitfaden zur Entwicklung und Implementierung von Zertifikatsprogrammen zur Förderung studentischer Gesundheitskompetenzen - Sting, Anna-Lena; Kehne, Dennis; Wobbe, Lena; Waltert, Carolin (Gesundheitskompetenzen in Hochschulen entwickeln - Studierende für ihre berufliche Zukunft stärken)

Leitfaden zur Planung von Datenanalysen zur Entscheidungsunterstützung im Produktmanagement - Grigoryan, Khoren; Martin, Lucas; Fichtler, Timm; Reinhold, Jannik; Asmar, Laban; Kühn, Arno; Dumitrescu, Roman (Vorausschau und Technologieplanung - 18. Symposium für Vorausschau und Technologieplanung)

Lerngegenstand, Modellierung, religionsdidaktisch - Reis, Oliver (WiReLex 02/2025)

Lessons Learned from the ProDaBi Project: Shaping Perspectives at the Intersection of Data, AI, and Education Towards Fostering AI and Data Science Literacy in Schools Across Disciplines. - Biehler, Rolf; Schulte, Carsten (Proceedings of the 1st Symposium on Integrating AI and Data Science into School Education Across Disciplines (AIDEA 1 2025), Salzburg, Austria)

Leveraging Self-Adaptive Systems and Generative AI for Personalizing Educational Serious Games: Architecture and Future Challenges - Bucchiarone, Antonio; Bonetti, Federico; Yigitbas, Enes (Proceedings of the 20th International Conference on Software Engineering for Adaptive and Self-Managing Systems (SEAMS 2025))

Lie groups of real analytic diffeomorphisms are L^1-regular - Glöckner, Helge (Nonlinear Analysis)
Let $M$ be a compact, real analytic manifold and $G$ be the Lie group of all real-analytic diffeomorphisms of $M$, which is modelled on the (DFS)-space ${\mathfrak g}$ of real-analytic vector fields on $M$. We study flows of time-dependent real-analytic vector fields on $M$ which are integrable functions in time, and their dependence on the time-dependent vector field. Notably, we show that the Lie group $G$ is $L^1$-regular in the sense that each $[\gamma]$ in $L^1([0,1],{\mathfrak g})$ has an evolution which is an absolutely continuous $G$-valued function on $[0,1]$ and smooth in $[\gamma]$. As tools for the proof, we develop several new results concerning $L^p$-regularity of infinite-dimensional Lie groups, for $1\leq p\leq \infty$, which will be useful also for the discussion of other classes of groups. Moreover, we obtain new results concerning the continuity and complex analyticity of non-linear mappings on open subsets of locally convex direct limits.

Linking social capital accumulation and information-seeking practices of international students in Germany - Teichert, Jeannine; Lin-Januszewski, Liang-Wen (Transitions: Journal of Transient Migration)
While existing studies have extensively explored various facets of international students’ experiences, a gap remains in understanding the connection between their social capital accumulation and information-seeking practices that shape the incoming students’ extended transition process. Successful information-seeking is not solely related to academic outcome; it is also influenced by the social capital resources available within and beyond familiar cultural groups. This article sheds light on how international students’ social capital accumulation shapes their information searches across various online and offline social networks. A total of ten international students were interviewed at the beginning and the end of their first semester in Germany during the 2022–23 academic year. The findings demonstrate that the incoming students’ information-seeking strategies and social capital accumulation change over time. The students rely on their previously established social connections offline and online when preparing for their departure. Upon arrival in Germany, the students continue to search for information within their linguistic and cultural familiar groups, but their information-seeking process shifts to local in-person contexts. During the semester, lecturers and fellow students become useful information sources at the university while the students develop confidence in their foreign language skills.

Liquiditätseffekte einer Vermögensteuer bei Mietwohnimmobilien - Maiterth, Ralf; Piper, Yuri; Sureth-Sloane, Caren (Steuer und Wirtschaft)
Dieser Beitrag untersucht Liquiditätseffekte einer Vermögensteuer bei Mietwohnimmobilien. Mithilfe von Daten einer Immobilien-Kapitalgesellschaft werden die Wirkungen einer Vermögensteuer auf die Cashflows aus der Vermietung von Wohnimmobilien simuliert. Der Detailgrad der Daten ermöglicht dabei Analysen auf Jahres-, Regional- und Baujahresebene. Ein Abgleich mit weiteren Immobiliendaten untermauert die Vergleichbarkeit und Aussagekraft der Analysen. Die Ergebnisse der Simulation zeigen, dass die Einführung einer Vermögensteuer den Cashflow aus dem Mietgeschäft erheblich reduzieren und zu Liquiditätsproblemen führen kann. Im Durchschnitt über alle Beobachtungen ergibt sich bei einem Vermögensteuersatz i.H.v. 2 % ein negativer Cashflow nach Berücksichtigung aller Kosten. Generell bedeutet dies, dass wachstumsorientierte Immobilien durch eine Vermögensteuer liquiditätsmäßig stärker belastet werden als mietrenditeorientierte Immobilien. Insbesondere in Großstädten mit hohen Immobilienwerten, aber verhältnismäßig geringen Mieten, können die Liquiditätseffekte mehr als dreimal so hoch ausfallen wie in ländlichen bzw. industriell-geprägten Regionen, was zu einem relativen Attraktivitätsverlust führen kann. Durch die Entkopplung der Vermögensteuer von den Mieterträgen zeichnet sich eine starke Abhängigkeit der Steuerlast von aktuellen Marktentwicklungen und dem Zinsumfeld ab, was eine zusätzliche Unsicherheit für Investoren darstellt. Diese steuerliche Unsicherheit könnte sich potentiell auf die Investitionsbereitschaft auswirken und sollte daher in politischen Diskussionen über die Wiedereinführung einer Vermögensteuer berücksichtigt werden.

Literarische Fiktionalität in der Vormoderne. Beiträge zu Problemen und Perspektiven

Livemusikkulturen, Virtualitäten und Metamorphosen: Perspektiven auf das kulturökonomische Konzept der Baumol’schen Kostenkrankheit - Flath, Beate (~Vibes - The IASPM D-A-CH Series)

Locally homogeneous Axiom A flows II: geometric structures for Anosov subgroups - Delarue, Benjamin; Monclair, Daniel; Sanders, Andrew (arXiv:2502.20195)
Given a non-compact semisimple real Lie group $G$ and an Anosov subgroup $Γ$, we utilize the correspondence between $\mathbb R$-valued additive characters on Levi subgroups $L$ of $G$ and $\mathbb R$-affine homogeneous line bundles over $G/L$ to systematically construct families of non-empty domains of proper discontinuity for the $Γ$-action. If $Γ$ is torsion-free, the analytic dynamical systems on the quotients are Axiom A, and assemble into a single partially hyperbolic multiflow. Each Axiom A system admits global analytic stable/unstable foliations with non-wandering set a single basic set on which the flow is conjugate to Sambarino's refraction flow, establishing that all refraction flows arise in this fashion. Furthermore, the $\mathbb R$-valued additive character is regular if and only if the associated Axiom A system admits a compatible pseudo-Riemannian metric and contact structure, which we relate to the Poisson structure on the dual of the Lie algebra of $G$.

Logics with probabilistic team semantics and the Boolean negation - Hannula, Miika; Hirvonen, Minna; Kontinen, Juha; Mahmood, Yasir; Meier, Arne; Virtema, Jonni (Journal of Logic and Computation)
Abstract We study the expressivity and the complexity of various logics in probabilistic team semantics with the Boolean negation. In particular, we study the extension of probabilistic independence logic with the Boolean negation, and a recently introduced logic first-order theory of random variables with probabilistic independence. We give several results that compare the expressivity of these logics with the most studied logics in probabilistic team semantics setting, as well as relating their expressivity to a numerical variant of second-order logic. In addition, we introduce novel entropy atoms and show that the extension of first-order logic by entropy atoms subsumes probabilistic independence logic. Finally, we obtain some results on the complexity of model checking, validity and satisfiability of our logics.

Low Temperature Emissive Cyclometalated Cobalt(III) Complexes - Krishna, Athul; Fritsch, Lorena; Steube, Jakob; Argüello Cordero, Miguel A.; Schoch, Roland; Neuba, Adam; Lochbrunner, Stefan; Bauer, Matthias (Inorganic Chemistry)
A series of CoIII complexes [Co(RImP)2][PF6], with HMeImP = 1,1′-(1,3-phenylene)bis(3-methyl-1-imidazole-2-ylidene)) and R = Me, Et, iPr, nBu, is presented in this work. The influence of the strong donor ligand on the ground and excited-state photophysical properties was investigated in the context of different alkyl substituents at the imidazole nitrogen. X-ray diffraction revealed no significant alterations of the structures and all differences in the series emerge from the electronic structures. These were probed via cyclic voltammetry and UV–vis spectroscopy, detailing the influence of the different alkyl substituents on the ground-state properties. All complexes are emissive at 77 K from a 3MC state, which exhibits lifetimes in the range of 1–5 ns at room temperature, depending on the alkyl substituent. Therefore, it is clearly shown that even small differences in the electronic structure have a large impact on the details of the excited state landscape. The observed behavior was rationalized by a detailed DFT analysis, which shows that the minimum-energy crossing point to the ground-state is located only slightly above the MC energy: Consequently, nonradiative decay to the ground state at room temperature is enabled, while at 77 K this path is prohibited, leading to low-temperature 3MC emission.

Machine learning of continuous and discrete variational ODEs with convergence guarantee and uncertainty quantification - Offen, Christian (Mathematics of Computation)
The article introduces a method to learn dynamical systems that are governed by Euler–Lagrange equations from data. The method is based on Gaussian process regression and identifies continuous or discrete Lagrangians and is, therefore, structure preserving by design. A rigorous proof of convergence as the distance between observation data points converges to zero and lower bounds for convergence rates are provided. Next to convergence guarantees, the method allows for quantification of model uncertainty, which can provide a basis of adaptive sampling techniques. We provide efficient uncertainty quantification of any observable that is linear in the Lagrangian, including of Hamiltonian functions (energy) and symplectic structures, which is of interest in the context of system identification. The article overcomes major practical and theoretical difficulties related to the ill-posedness of the identification task of (discrete) Lagrangians through a careful design of geometric regularisation strategies and through an exploit of a relation to convex minimisation problems in reproducing kernel Hilbert spaces.

Machine-Learning basierte Analyse von latenten Profilen des physikdidaktischen Wissens Machine-Learning-Based Analysis of Latent Profiles in Physics PCK - Zeller, Jannis; Riese, Josef (Zeitschrift für Didaktik der Naturwissenschaften)
Das fachdidaktische Wissen (FDW) stellt eine wichtige Komponente des Professionswissens von (angehenden) Lehrkräften dar. Es liegen bereits empirische Forschungsergebnisse zu Einflussfaktoren und zur Entwicklung des FDW sowie zur Bedeutung des FDW als Ganzem für Professionswissen und Qualität professioneller Handlungen vor. Für eine detailliertere Forschung zur Zusammenhangsstruktur zwischen FDW und der Performanz in prototypischen Handlungssituationen sind darüber hinaus differenziertere empirisch begründete Beschreibungen der inneren Struktur des FDW notwendig. Bisher sind entsprechende Ansätze allerdings zumeist primär theoretisch-normativ begründet oder auf hierarchische Betrachtungen beschränkt. Im vorliegenden Beitrag wird daher ein Ansatz zur nicht-hierarchischen datenbasierten Beschreibung latenter Kompetenzprofile des FDW orientiert an der Computational Grounded Theory vorgestellt. Dabei wird zunächst mithilfe eines Datensatzes von 846 Bearbeitungen des Physik-FDW-Testinstruments in überwiegend offenem Antwortformat aus dem Projekt ProfiLe-P+ eine latente Profilanalyse zur Untersuchung latenter FDW-Profile unter Fokus auf kognitive Anforderungen als empirisch trennbare Subskalen des FDW durchgeführt. Mithilfe von Topic Modeling werden anschließend Tendenzen in der Sprachnutzung der FDW-Profile untersucht. Um die Ergebnisse im Sinne der Computational Grounded Theory durch den Nachweis latenter Zusammenhänge zwischen den Testantworten der Proband:innen und der FDW-Profil-Zuordnung zu bestätigen, wird im Anschluss ein Machine-Learning-basiertes System zur automatisierten Zuordnung von Testbearbeitungen zu den FDW-Profilen erstellt. Es zeigen sich vier latente Kompetenzprofile mit nicht-hierarchischem Charakter. In einer längsschnittlichen Betrachtung wird abschließend die Entwicklung von Proband:innen im Kontext dieser FDW-Profile dargestellt. Die Ergebnisse bieten Ansatzmöglichkeiten zukünftig Untersuchungen der Zusammenhänge einzelner FDW-Komponenten und beispielsweise gezeigter Handlungsqualität auf Detailebene zu untersuchen.

Maddy, Penelope, Jouko Väänänen, Philosophical Uses of Categoricity Arguments, Cambridge University Press: Cambridge 2023 (Cambridge Elements). - Peckhaus, Volker (zbMATH Open, Zbl. 07771690)

Mastering Temporal Challenges – Zeitwohlstand und Zeiterleben iranischer Studierender in Deutschland - Philipper, Matthias (Geschlecht und Gerechtigkeit)

Materialien zum Schreiben im Psychologieunterricht - Scharlau, Ingrid; Schreiber, Christine (Psychologiedidaktik an allgemeinbildenden und beruflichen Schulen: Ein Lehrbuch mit Unterrichtsmaterialien)

Mathematics education for girls in Prussia 1890–1925 - Krüger, Katja; Werth, Gerda (The Journal of Mathematical Behavior)

Mathematikbezogenes Wissen, Einstellungen und Lerngelegenheiten als Einflussfaktoren der situativen Beobachtung und Wahrnehmung angehender frühpädagogischer Fachkräfte - Quack, Carolin; Bruns, Julia (Frühe Bildung)

Mathematische Grundbildung und rechnerische Grundkompetenzen im Feld der „Berufsbildung“ - Heisler, Dietmar; Sommer, Christian (Grundbildung und Habitus)
Zusammenfassung Für die Erklärung von sozialer Ungleichheit und des Einflusses sozialer Herkunft auf die Bildungsteilhabe von Individuen, auf ihre Bildungsbeteiligung und ihren Bildungserfolg wird oft auf die kultur- und bildungssoziologischen Ansätze Pierre Bourdieus zurückgegriffen. Dies gilt auch für den Bereich der Grundbildung, für die Erklärung von individuellen Leistungsunterschieden im Lesen, Schreiben und Rechnen. Unterschiede bei der Bildungsteilhabe und im Bildungserfolg werden von ihm u. a. auf die soziale Herkunft und die sozialen Praktiken in den sozialen Milieus zurückgeführt. Gerade Bourdieu versucht auch zu erklären, wie konkrete Anforderungen und Bildungsinhalte den Weg in schulische Curricula finden und so in Wechselwirkung mit den Strukturen des Bildungswesens und seinen sozialen Praktiken zur Reproduktion sozialer Ungleichheit in der Gesellschaft beitragen. Die These ist, dass die Inhalte und auch die Strukturen des Bildungswesens von einer bildungsnahen sozialen Oberschicht bestimmt werden, was den Bildungserfolg der Angehörigen dieser Schicht begünstigt und im Weiteren zur Reproduktion der Unterschiede zwischen den sozialen Milieus beiträgt. Der vorliegende Beitrag übersetzt dies in den Bereich der Grundbildung, vor allem der mathematischen Grundbildung und Vermittlung basaler mathematischer Grundkompetenzen. Ausgangspunkt ist die Frage, was unter mathematischer Grundbildung verstanden wird. Dafür wurden 21 Berufsschullehrkräfte in Interviews befragt. Die Ergebnisse der Befragung zeigen, dass mathematische Grundbildung von den Lehrkräften zu den Anforderungen von Bildungsgängen und Berufen kontextualisiert bzw. in Relation gesetzt wird. Als mathematische Grundkompetenzen werden Wissen und Fähigkeiten verstanden, die notwendig sind, um einen gegenwärtigen Bildungsgang bewältigen zu können, und die in vorangegangenen Bildungsgängen erworben wurden. Folglich werden mathematische Grundkompetenzen, die für die Bewältigung beruflicher Bildungsgänge notwendig sind, an den Klassenstufen im allgemeinbildenden Schulsystem festgemacht, deren Inhalte für den jeweiligen Bildungsgang als Voraussetzung oder grundlegend zur Bewältigung seiner Anforderungen und Inhalte betrachtet werden. Das hat zur Folge, dass es zum einen kein einheitliches Verständnis zu mathematischer Grundkompetenz bzw. sogenannten basalen Rechenfähigkeiten gibt. Vielmehr werden diese an unterschiedlichen Klassenstufen und Leistungsniveaus festgemacht. Unter Rückgriff auf die Überlegungen Bourdieus bedeutet dies zum anderen, dass die beruflichen Schulen die soziale und herkunftsbedingte Selektivität, die bislang vor allem am allgemeinbildenden Schulsystem kritisiert wird, über ihre Bildungsgänge fortschreiben, indem aus den Bildungsgängen heraus formale und inhaltliche Anforderungen formuliert werden, die den konkreten Bezug zu bestimmten Klassenstufen und Schulformen nehmen. Dies kann nun als Ausdruck oder Hinweis auf die Selektions- und Allokationsfunktion von Schule interpretiert werden. Allerdings erscheint es insofern kritisch, da die beruflichen Schulen seit ihren Reformen in den 1970er Jahren doch den Anspruch erheben, deutlich durchlässiger und weniger sozial selektiv zu sein als die allgemeinbildenden Schulen.

Maximizing the benefits of student-generated drawing for real-world problem solving - Schönherr, Johanna; Mayer, Richard E. (Contemporary Educational Psychology)

Mechanical joinability of microstructurally graded structural components manufactured from hypoeutectic aluminium casting alloys - Neuser, Moritz; Schlichter, Malte Christian; Hoyer, Kay-Peter; Bobbert, Mathias; Meschut, Gerson; Schaper, Mirko (44th Conference of the International Deep Drawing Research Group (IDDRG 2025))
Lightweight design is a driving concept in modern automotive engineering to minimize resource consumption over a vehicle's lifecycle through multi-material design, which relies on the use of joining techniques in car body fabrication. Multi-material design and the increasing trend towards producing large structural components using the megacasting process pose considerable challenges, particularly in the mechanical joining of aluminium-silicon (AlSi) castings. These castings typically exhibit low ductility and are prone to cracking when mechanically joined. Based on the excellent castability of hypoeutectic AlSi alloys, these are applied in sand casting and die casting as well as in megacasting. With a silicon content between 7 wt% and 12 wt%, these AlSi-alloys have a plate-like silicon phase that initiates cracks during mechanical joining. To enhance the joinability of castings, the research hypothesis is that improved solidification conditions enable a significant modification in the microstructure and therefore, increase the mechanical properties. During the manufacture of the castings using the sand casting process, the solidification conditions within the structural elements are varied to modify the microstructure to obtain castings with graded microstructure. The castings are evaluated using mechanical, microstructural and joining testing methods and finally, a microstructure-joinability correlation is established.
Keywords: Joining; Casting; Self-pierce riveting; Aluminium casting alloy

Mechanical properties and joinability of the near-eutectic aluminium casting alloy AlSi12 - Neuser, M.; Holtkamp, P.-K.; Hoyer, K.-P.; Kappe, F.; Yildiz, S.; Bobbert, M.; Meschut, G.; Schaper, M. (Proceedings of the Institution of Mechanical Engineers, Part L: Journal of Materials: Design and Applications)
One of the most important strategies for reducing CO 2 emissions in the mobility sector is lightweight construction. In particular, the car body offers several opportunities for weight reduction. Multi-material designs are increasingly being applied to select the most suitable material for the respective load and ultimately achieve synergy effects. For example, aluminium castings are used at the nodes of a spaceframe body. Subsequently, these are joined with profiles to form the bodyshell. To join different materials mechanical joining techniques, such as semi-tubular self-piercing riveting, are deployed. According to the current state of the art, cracks occur in the aluminium castings during the mechanical joining process as a result of the high degree of deformation. Although the aluminium casting alloys of the AlSi-system exhibit low ductility, these alloys reveal excellent castability. In particular, the ability to cast thin structural parts is enabled by the low liquidus point of the near eutectic aluminium casting alloys. This study addresses the mechanical joining properties of the near eutectic aluminium casting alloy AlSi12, depending on different microstructures. These are achieved by annealing processes and modifying agents. Through an adapted heat treatment, the previously lamellar morphology can be transformed into a globular morphology, which leads to increased ductility and prevents the formation of cracks during the self-piercing riveting (SPR). The joinability is investigated using different die geometries, whereas the joint formation is analysed regarding crack initiation. To evaluate the increased ductility, microstructural and mechanical tests are performed and finally, a microstructure-joinability correlation is established.

Mechanical properties and joinability of the near-eutectic aluminium casting alloy AlSi12 - Neuser, Moritz; Holtkamp, Pia Katharina; Hoyer, Kay-Peter; Kappe, Fabian; Yildiz, Safak; Bobbert, Mathias; Meschut, Gerson; Schaper, Mirko (The Journal of Materials: Design and Applications, Part L)
One of the most important strategies for reducing CO2 emissions in the mobility sector is lightweight construction. In particular, the car body offers several opportunities for weight reduction. Multi-material designs are increasingly being applied to select the most suitable material for the respective load and ultimately achieve synergy effects. For example, aluminium castings are used at the nodes of a spaceframe body. Subsequently, these are joined with profiles to form the bodyshell. To join different materials mechanical joining techniques, such as semi-tubular self-piercing riveting, are deployed. According to the current state of the art, cracks occur in the aluminium castings during the mechanical joining process as a result of the high degree of deformation. Although the aluminium casting alloys of the AlSi-system exhibit low ductility, these alloys reveal excellent castability. In particular, the ability to cast thin structural parts is enabled by the low liquidus point of the near eutectic aluminium casting alloys. This study addresses the mechanical joining properties of the near eutectic aluminium casting alloy AlSi12, depending on different microstructures. These are achieved by annealing processes and modifying agents. Through an adapted heat treatment, the previously lamellar morphology can be transformed into a globular morphology, which leads to increased ductility and prevents the formation of cracks during the self-piercing riveting (SPR). The joinability is investigated using different die geometries, whereas the joint formation is analysed regarding crack initiation. To evaluate the increased ductility, microstructural and mechanical tests are performed and finally, a microstructure-joinability correlation is established.
Keywords: aluminium; casting; microstructure; joinability; self-piercing riveting